PENGARUH SUKROSA DAN GLUTAMIN PADA KULTUR ANTER Solatium khasianutn CLARKE - Gandawidjaja, Djunaedi (Research Center for Biology-Indonesian Institute of Sciences, 1998)
Effect of Sucrose and Glutamine on Anter Culture ofSolanum khasianum Clarke, Djunaedi Gandawidjaja.Anther ofSolanum khasianum Clarke were cultured on MS medium enriched with sucrose (30, 60, 75, 90 g/l)combined with glutamine (0, 200, 400, 600 mg/l)or with sucrose (60 g/1) combined with glutamine at low concentrations (0, 0.5,2.5, 5.0,10.0,20.0,50.0 mg/l).Callus formation was affected by the interaction of sucrose and glutamine. Callus formation decreased with the increasing concentration of sucrose or glutamine. Combination of sucrose and glutamine was unable to regenerate planletfrom the callus.